Crude Antigen Cystisercus Taenia Saginata Isolat Bali untuk Deteksi Sistiserkosis pada Sapi - Lubis, Hertati Anriani; Damriyasa, I Made; Dharmawan, Nyoman Sadra (Veterinary Science and Medicine Journal; Vol 2 No 1 (2014), 2014)
The purpose of this study was to evaluate Taenia saginata cystisercus antigen for the detection of bovine cysticercosis. Taenia saginata cysticercus antigen was derived from local isolates, obtained from the experimental infection of Taenia saginata tape worms from Bali. The research was done by ELISA (Enzyme Linked Immunosorbent Assay) optimized by determining the optimal concentration of antigen, the optimal dilutions of serum and the optimal dilutions of conjugate. The results showed that Taenia saginata cysticercus crude antigen (Bali isolate) are antigenic and can be used to detect cattle cysticercosis. Optimal concentration of antigen: 2 ug/ml, optimal dilutions of serum: 1:80 and optimal dilution of conjugate: 1:4000.
Keywords: Taenia saginata cysticercus; Antigen; ELISA